Effect of tunneling cracks on structural property degradation of wind turbine blades. (15th July 2021) - Castro, Oscar; Branner, Kim
Abstract: In this study, a multi-scale structural approach is used to analyze the effect of tunneling cracks on the structural response of wind turbine blades. In this approach, a 2D finite-element-based cross-section analysis and a continuum damage mechanics model are combined to efficiently predict the variation in cross-section stiffnesses and natural frequencies of the blades as a function of the tunneling crack density. By applying this approach to an 86.35-meter wind turbine blade, it is shown how the level of variation of these structural properties depends not only on the degradation of the material properties due to the presence of tunneling cracks but also on the spatial characteristics of the different cross-section regions along the blade, such as spar caps, trailing-edge panels, etc.